Machiavellianism and psychopathy affect sleep quality in people with affective disorders and mentally healthy individuals - Schönthaler, Elena M. D.; Dalkner, Nina; von Lewinski, Dirk; Reininghaus, Eva Z.; Baranyi, Andreas (Frontiers in Psychology, 2023)
Introduction Deteriorated sleep quality is a predisposing factor and symptom of affective disorders (AD). It is important to investigate factors driving the relationship between sleep and AD, such as personality traits. Previous research has shown that personality traits such as the Dark Triad personality traits (DT) narcissism, Machiavellianism, and psychopathy are associated with sleep problems and AD. The current study examined the moderating influence of the DT in the relationship between AD [versus healthy controls (HC)] and sleep quality. Methods Data of 657 individuals (267 HC, 390 AD; 483 female, 166 male, eight diverse; Mage = 34.87, SDage = 13.86) were collected in an online survey, which administered the Pittsburgh Sleep Quality Index and the Short Dark Triad questionnaire. Results Moderation analyses controlling for age and gender revealed that Machiavellianism (b = −0.76, p < 0.05, R2 = 0.35) and psychopathy (b = −1.15, p < 0.05, R2 = 0.35), but not narcissism (b = −0.20, p = 0.620, R2 = 0.35), had a negative effect on sleep quality. Specifically, this effect is more pronounced in the HC group, but sleep quality is generally worse in AD. Conclusion Our findings indicate that Machiavellianism and psychopathy should be considered in the prevention and treatment of AD-associated sleep problems. Particularly, monitoring these traits could help to implement timely measures for the prevention of sleep problems, such as psychoeducation and sleep hygiene. The results highlight the role of personality in the aetiopathogenesis of AD and require further differentiation to examine the underlying pathways between the DT, sleep, and AD.